Paciente de sexo femenino de 48 años de edad con hipotiroidismo subclínico y obesidad. - Moran Burgos, Jonathan Mario (2020)
Subclinical Hypothyroidism is currently one of the diseases Little considered, that is, it is an ignored pathology, despite the fact it only requires verification of elevated TSH and T4 values in normal ranges for its diagnisis, which is why doctors are recommended to increase the frequency of performing these tests, to achieve a timely diagnosis and apply treatment. The present clinical case, a 48-year-old female patient with Subclinical Hypothyroidism and Obesity with a family history of maternal diabetes and a hipertensive father, who comes to the IESS hospital outpatient clinic for presenting weight gain and fatigue for no apparent reason. Accompanied by laboratory results where TSH reports alterations with higher tan normal values and normal T4. The described case will have the execution of a personalized nitritional plan for the patient with the aim of rectifying their eating style and controlling future problems with Subclinical Hipothyroidism. Nutritional intervention gave a favorable result for the patient, showing in the follow-up and monitoring that an improvement in antropometric andicators was carried auto ver a period of three months, such as the weight of 82 kg decreased to 69 kg, waist circumference from 108 cm to 96 cm, hip circumference from 122 cm to 111 cm, and the BMI from 31,2 kg/m2 to 26.3 kg/m2, in addition to reaching normal values of triglycerides and TSH.